LEVEL OF CARDIORESPIRATORY FITNESS OF ADMINISTRATIVE DEPARTMENT RUNNERS (Fiep Bulletin - online, 2013)
The concept of physical fitness was defined as a set of attributes that people have or achieve and is related to the ability to perform physical activity, represented by elements related to the activities, and physiological health. (ACSM, 2007). Are physical fitness tests, exercise programs, instruct individuals as to their fitness as State health standards, to have the data needed to conduct the exercise prescription, initial data collection in the future comparison will give a reply how to advance to the final of the training program and motivation about the purpose and the risk of the individual laminate (ACSM2003). The subjects were 11 individuals, practitioners of street racing and Administrative Department official of the higher education institution in Rio de Janeiro, with ages between 25-46 years. The average age was of 34.71 + 8.86 years (men) and 32.5 + 5.75 years (women). The VO ² Max referred to this group of women (31.8 + 1.57 ml/Kg/min) was underestimated, even though half the group is classified as insufficiently active, reached a higher value in the test cycle ergômetro (33.82 +  4.23 ml/Kg/min). The Group of men earned an average of maximum oxygen uptake capacity achieved in test (45.84 + 9.13 ml/Kg/min) below the predicted values (51.4 + 11.6 ml/Kg/min). On the basis of the data, there appears to be a non-conformity between the direct and indirect method to get the value of the maximum consumption of oxygen. Towards women, the direct method seems to underestimate the physical capacity of the volunteers.
Keywords: physical fitness; maximal oxygen uptake; exercise stress test